Antiurolithiatic and antioxidant activity of Abies webbiana leaves on ethylene glycol-induced urolithiasis in rats (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
One major issue is the recurrence of urolithiasis. The majority of the treatments were derived from plants and worked well. Many important active phytochemicals are found in Abies webbiana. This study evaluates the protective potential of Abies webbiana in Wistar albino rats with ethylene glycol-induced urolithiasis. 0.75 percent ethylene glycol (v/v) for a period of 28 days given to induce the formation of renal calculi, Cystone (750 mg/kg) use as standard drug and leave extract (200 mg/kg and 400 mg/kg) test drug. The standard and test drug administer on days 15 through 28. Parameters such as Oxalate, Uric Acid, Blood Urea Nitrogen, Potassium, Creatinine, Calcium, Urea and histopathology of Kidney were assessed. The present study significant antiurolithiatic and antioxidant property of test drug at 400 mg/kg. The extract's flavonoids, terpenoids, and alkaloids may be the cause of these effects. In addition to maintaining dose-dependent levels of oxalate (P<0.0001), urea (P<0.05), uric acid (P<0.001), creatinine (P<0.05), and lipid peroxidation (P<0.01), the extract can lessen the buildup of chemicals that cause stones. The extract was quite successful in preserving the histological integrity. Documentary proof of Abies webbiana's antiurolithiatic properties has been presented in this study.